Indledende note om demokrati-begrebet - Agamben, Giorgio; Eggers, Nicolai von (Slagmark - Tidsskrift for idéhistorie, 2015)
In this text, Giorgio Agamben argues that the concept of democracy attests to a political, ontological amphibology: on the one side, democracy describes a constitution of a political order (and in this sense it belongs to public law); on the other side, democracy is a certain form of administration (in which case it belongs to administrative practice). It is argued that this amphibology can be located in the political theories of Aristotle and Jean-Jacques Rousseau who have been instrumental in forming our present conception of politics. Consequently, we misunderstand the fundamental nature of politics, and any hopes of genuine political life must therefore break with this tradition of Western political philosophy.